Molecular detection of beneficial hyphal soil-born microorganisms in different soil types in areas infested with parasitic broomrapes - Orobanche cumana Wallr. and Phelipanche ramosa L. in Bulgaria - Kirilova, Ina; Hristeva, Tsveta; Bozhinova, Radka; Denev, Iliya; Docheva, Margarita; Yonchev, Yonko (Journal of BioScience and Biotechnology, 2019)
Molecular markers and classic microbiological approaches for assessment of the population density and biodiversity of beneficial hyphal soil-born microorganisms (species from order Actinomicetalеs and arbuscular mycorrhizal fungi from Glomeromycota). Seven different soil types infested by parasitic broomrapes - Orobanche cumana Wallr. and Phelipanche ramosa L. were studied. The soil samples were collected from seventeen regions in Northern and Southern Bulgaria. Soil types were defined as: Chromic Cambisols; Chromic Luvisols; Calcic Vertisols; Mollic Fluvisols; Rendzic Leptosols; Chernozems - Calcic and Haplic, based on agrochemical characteristics. We found that the Chromic Luvisols soils have the highest population density of beneficial microorganisms and a high degree of colonization with arbuscular mycorrhizal fungi, followed by Mollic Fluvisols soils. Two main species of arbuscular mycorrhizal fungi were identified by molecular markers: Glomus intraradices and G. mosseae. The highest density of beneficial streptomycetes was found Chromic Luvisols soils. Based on molecular markers five species of Streptomycetes were identified namely: Streptomyces ambofaciens, S. aureocirculatus, S. carnosus, S. fasiculatus, S. griseorubens. Number of other hyphal fungi were also recorded from genera Aspergillus, Penicillium, Trichoderma, Fusarium, Mucor. Molecular identification of the strains of those fungi, however will require metagenomics approach. The results obtained will allow us to develop new strategy for using beneficial hyphal microorganisms to control parasitic weeds from Orobanchaceae.